Implementation of Religious Moderation in Higher Education - Oktrigana Wirian; Hasan Bakti Nasution; Mohammad Al Farabi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
This study aims to examine the implementation of religious moderation at HKBP Nommensen University Medan as a case study. This research uses a qualitative approach with a type of phenomenology. Data were obtained through in-depth interviews, participatory observations, and documentation studies. The informants consisted of lecturers, education staff, and students from various religious backgrounds. The results of the study show that religious moderation in the campus environment has been applied culturally and practically, as seen from the attitude of tolerance, the provision of interfaith worship facilities, and inclusive learning. However, the implementation has not been followed by a formal policy or a structured evaluation system. This condition makes the sustainability of moderation practices dependent on the values of the community and current leadership. In conclusion, the campus has become a participatory religious moderation space, but it is necessary to strengthen institutions in the form of written regulations and systematic evaluation to ensure the sustainability and quality of the implementation of moderation values in the future.